Do Spider Diversity and Assemblages Change in Different Contiguous Habitats? A Case Study in the Protected Habitats of the Humid Chaco Ecoregion, Northeast Argentina - Rubio, Gonzalo Daniel (2008)
Spiders are a megadiverse group that can be useful indicators of the overall species richness and health of biotic communities. The spider diversity in subtropical forests of the Neotropical region are not yet well known, especially in Argentinean subtropical forests where systematic Þeldwork has not been done until recently. The Great Chaco is very important as the unique dry subtropical forest of the earth, but it is suffering increasing degradation by the advance of agriculture. Spider communities have been shown to be more directly inßuenced by vegetation architecture than vegetation species composition. In this study, we aim to assess whether spider diversity and assemblages change in adjacent habitats with different types of vegetation. We compare the diversity and spider assemblages in two different contiguous protected habitats (hygrophilous woodland and savannah parkland) of the Mburucuya´ National Park, (Humid Chaco ecoregion). Seasonal samples were obtained using three types of sampling methods: pitfall trapping, beating, and manual litter extraction. The spider assemblages were different in the studied areas, and the abundance, diversity, evenness, and species richness were higher in the hygrophilous woodland than the savannah parkland. These differences in spider diversity and assemblages indicate that both types of habitats are important if the biodiversity is to be conserved in the Chaco ecoregion, where different types of habitat are shown as a patchy distribution.